(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Dermatological diseases represent one of the most prevalent health issues globally, significantly affecting patients’ quality of life and imposing a considerable burden on healthcare systems. Effective medication adherence is critical for achieving optimal therapeutic outcomes in dermatology, particularly for chronic conditions such as eczema, psoriasis, and acne. Community pharmacists, as easily accessible healthcare professionals, are uniquely positioned to promote adherence through patient counseling, education, and follow-up. However, limited dermatological training and systemic barriers often hinder their ability to provide effective care. Objective: This study aimed to evaluate the effectiveness of community pharmacists in improving medication adherence among dermatological patients in Lahore, Pakistan. It further sought to identify common dermatological disorders managed in community pharmacy settings, assess pharmacists’ roles in patient counseling and education, and examine challenges encountered in implementing adherence-promoting interventions and Value-Added Services (VAS). Methods: A descriptive cross-sectional study design was employed across multiple community pharmacies in Lahore. Data were collected from 347 licensed community pharmacists through a structured, closed-ended questionnaire comprising five sections addressing demographics, common dermatological conditions, pharmacist interventions, adherence programs, and operational challenges. Statistical analyses were conducted using IBM SPSS version 26.0, applying descriptive statistics, Chi-square, Friedman Test, Pearson correlation, ANOVA, and Spearman’s rho to evaluate relationships and significance at p < 0.05. Results: Findings revealed that community pharmacists frequently encounter dermatological conditions such as dry skin (91.9%), sunburn (87%), fungal infections (57.1%), and eczema dermatitis (57.3%), with significant seasonal variations (χ² = 763.120, p < .001). The majority (76.1%) of pharmacists held a positive attitude toward medication adherence programs, acknowledging their impact on patient compliance and quality of life. Pearson correlation analyses confirmed a strong relationship between pharmacist interventions and improved adherence (r = 0.63, p < .001). About 75.8% of pharmacists demonstrated good knowledge of their roles in promoting adherence, with no significant association found between knowledge level and demographic variables. Despite positive engagement, pharmacists reported multiple challenges, including lack of patient trust (47.3%), insufficient training (45%), absence of counseling areas (49.3%), and inadequate remuneration (44.1%). Spearman’s rho analysis identified significant correlations among these barriers (p < .05), highlighting structural and professional limitations within community pharmacy practice. Conclusion: The study underscores the pivotal role of community pharmacists in improving medication adherence among dermatological patients. While pharmacists exhibit strong commitment and awareness, systemic barriers—such as limited access to patient records, inadequate training, and absence of standardized VAS frameworks—impede their effectiveness. Strengthening pharmacist education, fostering interprofessional collaboration, and implementing standardized adherence programs could substantially enhance patient outcomes and healthcare efficiency. Targeted interventions are recommended to integrate pharmacists more effectively into dermatological care pathways.